2013
DOI: 10.7243/2052-6962-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Possible red blood cell damage due to iatrogenic transfusion filter-related mistakes during blood transfusion

Abstract: Background: Red cell concentrates are usually transfused through a transfusion filter. Iatrogenic accidents can occur in which the red blood cell concentrate is transfused through the infusion filter by mistake. Therefore, we examined the extent of red blood cell damage in red cell concentrates transfused through transfusion and infusion filters ex vivo. Methods: We evaluated red blood cell damage using lactate dehydrogenase, free hemoglobin, and erythrocyte membrane phosphatidylserine expression in red cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…A transfusion set-pass experiment, unique to us, was used to assess RBC solution quality. We previously reported that RBC solution had hemolytic activity after filtration, which was mainly due to poor temperature control during vehicle transport that may increase the LDH levels in RBC solutions after transport, even if LDH is not a problem due to transfusion set-pass [25]. This emphasizes the importance of measuring LDH, which passes through the transfusion filter before transfusion in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…A transfusion set-pass experiment, unique to us, was used to assess RBC solution quality. We previously reported that RBC solution had hemolytic activity after filtration, which was mainly due to poor temperature control during vehicle transport that may increase the LDH levels in RBC solutions after transport, even if LDH is not a problem due to transfusion set-pass [25]. This emphasizes the importance of measuring LDH, which passes through the transfusion filter before transfusion in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Part of the WBs in the packs were passed through a filter, transfusion set (Terumo Co. Ltd., Tokyo, Japan). 10 The WB samples in the no-travel, flight, and non-flight groups, which were centrifuged at 3500 rpm for 10 min, underwent measurements of lactate dehydrogenase (LDH) and other biochemical indices and also subjected to coagulation tests.…”
Section: Processing Of the Blood Samplesmentioning
confidence: 99%